Development of empathy and ethical values through role-playing games as innovation for education in values - Carnicero Pérez, Jose David; Moreno-Rodríguez, Ricardo; Felgueras Custodio, Nerea (IJERI: International Journal of Educational Research and Innovation, 2023)
For some authors, the development of empathy is a central aspect of the development of ethical values. Role-playing games can be the ideal vehicle to transfer learning from fiction to reality. The present study analyzes in an exploratory and descriptive way the scores obtained in the Test of Cognitive and Affective Empathy (TECA) of a total sample of 208 participants. Although no major differences were found between those who had previously participated in role-playing games and those who had not, there was a tendency to obtain higher mean scores than those obtained by the TECA through its scales.